Effects of Modified Atmosphere Packaging on Selected Phenomena Affecting Quality of Fresh, Edible Bamboo Shoots - Probo Y Nugrahedi; Maria Lusiani; Stefan T Persijn (Indonesian Association of Food Technologists, 2004)
Changes in phenomena affecting quality of fresh bamboo shoots (Dendrocalamus asper, Schultes f.) due to modified atmosphere packaging were evaluated. After harvest bamboo shoots were peeled, and stored in the open (unpacked) or packaged in polyvinyl chloride wrap (thickness 5µm) or polypropylene bags (thickness 15 µm) at two different temperatures (9 and 28 oC) and shelf life was determined. Unpacked samples had very high weight losses (5% per day) at both temperatures limiting their shelf life to less than 2 days. Both types of packaging reduced water loss significantly (polyvinyl chloride: 0.5% per day at both temperatures, polypropylene: 0.09% and 0.14% at 9 and 28 oC respectively). Samples stored at room temperature started to discolor within 1-2 days while packed samples in the refrigerator showed the first signs of discoloration only after 5-7 days of storage. Refrigeration was also effective to inhibit fungal growth. Our results show that application of cold storage or packaging alone yield no, or only a limited extension of shelf life but their combined application yields a shelf life extension till 2 weeks.